Revisiting Inuit Qaujimajatuqangit: Inuit knowledge, culture, language, and values in Nunavut institutions since 1999 - Lévesque, Francis (Études/Inuit/Studies, 2014)
The Government of Nunavut and the Nunavut Land Claims Agreement organizations have been making a lot of effort to integrate Inuit qaujimajatuqangit (IQ) into their operations, institutional structures, and policies since the creation of the territory in 1999. This paper describes some of the ways in which IQ has been integrated into the operations, structures, and policies of Nunavut since 1999. It also proposes a broader discussion about the impacts of Western bureaucratic institutions on IQ, and highlights that IQ also impacts Nunavut operations and institutions. In this paper, I argue that IQ is not so much a practice of resistance to the colonial order, as some have suggested, but rather a way for Inuit to assume control of these structures to adapt them to their own use. Although IQ has still relatively limited influence, it has the potential, in the long run, to reshape Nunavut institutions and make them more representative of Inuit culture.